Changes of mountain glaciers in the Southern and Northern Hemispheres over the past 160 years - V. Kotlyakov M.; L. Chernova P.; A. Muraviev Ya.; T. Khromova E.; N. Zverkova M.; В. Котляков М.; Л. Чернова П.; А. Муравьев Я.; Т. Хромова Е.; Н. Зверкова М. (Ice and Snow, 2017)
Changes of the glacier areas were analyzed. Rates of the area reduction of glaciers and glacier systems were compared over the course of the past 160 years as well as during shorter time intervals for the same period. On average for the whole period, the glacier areas decreased by a few tenths of a percent from the original in a year. Note, that this value was formed by rates for periods of the glacier retreating and advancing which were comparable by their intensities with rates from tenths of a percent to several percents of area in a year. In the first and the last thirds of the 20th century, when a rise of the air temperature decelerated, a number of advancing glaciers increased in both hemispheres. During these periods the same glaciers advanced (up to 25% of the total quantity of the investigated glaciers in the Alps). The second third of the 20th and the begin‑ ning of the 21st century were characterized by intensification of the temperature rise, and as the consequence of that, the number of advancing glaciers decreased, and rates of the area reductions increased over the whole globe. This dynamics was in a good agreement with the sea ice fluctuations in both, the Arctic and Antarctic regions, where the ice coverage increased in the 1960–1970 and in the second tenth of XXI century. So, decel‑ eration of the climate warming in that time was followed by increasing of the Arctic and Antarctic sea ice coverage and by deceleration of the area reduction of the mountain glacierization in some regions. Исследованы скорости перемещения фронта и изменения площади ряда ледников за последние 160 лет. В этот период на общем фоне сокращения горного оледенения число наступающих ледников возрастало при замедлении роста температур воздуха в первой и последней третях ХХ в. Во второй трети ХХ и начале XXI вв. отступание ледников усиливалось вместе с заметным ростом температуры воздуха. Такие изменения согласуются с колебаниями площади морских льдов, которая в 1960–70-х годах возрастала, а в середине ХХ и начале XXI вв. ...